Observations on Deep Sea Demersal Resources in the Exclusive Economic Zone off Southwest Coast of India - P.A., Panicker; M.R., Boopendranath; M., Syed Abbas (Fishery Technology, 2025)
Results of 60 deep sea trawling operations conducted from FORV sagar sampada in the Exclusive Economic Zone off southwest coast of India, during cruise Nos. 97 and 99, January-April 1992, are presented in this paper with a view to substantiate or update the existing database on deep sea resources. 95.7 tonnes of fish and shellfish were landed during a total trawling effort of 55 h 30 min spread over 17-7Â°N lat, within 50-500 m depth. Nemipterus was the most dominant species contributing 66.7% of the total landings, followed by Decapterus sp. 9.7%, Priacanthus sp.5.9%, Centrolophus sp. 5.0%, Chlorophthalmus sp. 2.3%, large elasmobranchs 1.2%, Saurida sp. 1.2%, Trichiurus auriga 1.1%, deep sea prawns 0.8%, Sphyraena sp. 0.5%, deep sea lobster 0.4%, cephalopods 0.4%, high value perches 0.2%, Neopinnula sp. 0.2%, Psenes sp. 0.2%, swarming crabs (Charybdis sp.) 0.2%, catfish 0.1% and miscellaneous fish 3.9%. distribution of CPUE for total catch and for quantitatively and economically significant species groups are given by depth and latitude zones.